Pengaruh Fear of Missing Out ( FOMO ) terhadap Implusive Buying Saham pada Generasi Z - Saputra, Ihksan; Aulia, Prima (AHKAM, 2024)
This research aims to determine the effect of fear of missing out (fomo) on impulsive buying stock in generation z. This research uses qualitative methods with a correlational qualitative design. The data collection technique uses purposive sampling. The sample in this study was 272 respondents. This research instrument uses a fear of missing out (fomo) scale which is structured based on the fear of missing out (fomo) aspects according to Sette et al. (2020), as well as an impulsive buying scale based on aspects developed by Verplanken & Herabadi (2001). The results of the analysis used simple linear regression analysis and the results showed that fear of missing out (fomo) had a positive and significant effect on impulsive stock buying in generation z.